Представництво інтересів малолітніх чи неповнолітніх осіб посадовими особами закладів для дітей-сиріт і дітей, позбавлених батьківського піклування - Іліопол, Інна Михайлівна; Іліопол, І. М.; Iliopol, Inna M. (Херсон : Видавничий дім «Гельветика», 2019)
Стаття присвячена дослідженню процесуальних особливостей представництва у суді. Досліджено законодавче регулювання та судова практика стосовно питань представництва органів та осіб, яким законом надано право звертатися до суду в інтересах інших осіб, а саме в інтересах дітей-сиріт та дітей, позбавлених батьківського піклування.

The article is devoted to the study of the procedural features of representation in court. The legislative regulation and judicial practice on the representation of bodies and persons who are granted the right to appeal to the law in the interests of other persons, namely in the interests of orphans and children deprived of parental care, are examined. For many years in Ukraine there has been a problem of violation of property and housing rights of children of vulnerable categories. Children who, due to life circumstances, ended up in institutions for orphans and children deprived of parental care, face the problem of loss or lack of their own housing or property and, when they reach the age of majority or 23 years old, find themselves on the street. The issue of preventing human rights violations is still relevant in our country. Human trafficking, homelessness, begging, child crime, abuse and domestic violence, labor exploitation, fraudulent acts against elderly people and people with disabilities (for example, the illegal alienation of property), violation of the rights of minors or minors – this is not the whole list of offenses today. Consequently, crimes against a person require effective measures to prevent them, and people who find themselves in a difficult situation need the support and protection of the state. The civil procedural legislation of Ukraine contains a provision under which state authorities, local governments, individuals and legal entities have the right to apply to the court with statements about the protection of the rights, freedoms and interests of others, state or public interests and take part in such cases.
Іліопол І. М. Представництво інтересів малолітніх чи неповнолітніх осіб посадовими особами закладів для дітей-сиріт і дітей, позбавлених батьківського піклування / І. М. Іліопол // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 34. – С. 81-85.
Keywords: цивільний процес; представництво в суді; діти-сироти; діти; позбавлені батьківського піклування; неповнолітні особи; малолітні особи; житлові права; civil process; representation in court; orphans; children deprived of parental care; minors, juveniles; housing rights; Research Subject Categories::LAW/JURISPRUDENCE